Understanding Employee Perception to Promote Management Level Workforce Development for Roofing Contractors. Issue 2 (3rd April 2023) - Gajjar, Dhaval; Lucas, Jason; Davis, David
ABSTRACT: The roofing industry faces severe workforce shortages, especially for management positions. This study fills an essential gap to the existing body of knowledge by providing critical data for the roofing sector by identifying areas of improvement to attract and retain management professionals in the roofing industry. The study used a survey instrument to collect and analyze the roofing professional's perspective regarding various satisfaction, attraction, and retention factors in the roofing industry. The study also examines other factors such as the impact of experience and education on compensation and the career recommendation for the future workforce. Findings suggest that overall work and yearly compensation were key factors for attraction and retention. The areas where the roofing industry needs improvement include the costs of comprehensive benefits and a well-defined path for promotion and career evolution, two key factors that studies show younger workers are looking for when choosing an industry.